ANALISIS INTERVENSI FUNGSI STEP PADA HARGA SAHAM (STUDI KASUS SAHAM PT FAST FOOD INDONESIA Tbk) - Sari, Ratna Novita; Mariani, Scolastika; Hendikawati, Putriaji (Unnes Journal of Mathematics, 2016)
The analysis of the intervention is analysis a time series data that is affected by events outside the control of which may result in a change in the time series. Intervention analysis is used to analyze the data time series data of known intervention time. The main objective of this research is to determine the best intervention model on price of stock data PT Fast Food Indonesia Tbk period December 2013-January 2014, so the best forecasting method can be used to predict price of stock data PT Fast Food Indonesia Tbk for the next period with the help of SAS software program. Based on the analysis of the obtained the best intervention model that is a model of ARIMA (2,4,2) with the order of b = 20, s = 5, r = 0. The model of forecasting results obtained with the model of the step function intervention shows that the value of his predictions are within the threshold interval 95% confident with the results of the Eastern 70.82, MSE amounting to 386.94, and the RMSE of 19.671. So the forecast results can be used to estimate the daily price of stock data PT Fast Food Indonesia Tbk on 23 January 2014 to 20 February 2014 post intervention due to the occurrence of a policy dividend that caused significantly decreased just around the time the intervention only.